2005
DOI: 10.1007/s10658-005-3120-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the causal agent of pistachio dieback in Australia

Abstract: Symptoms associated with pistachio dieback in Australia include decline (little or no current season growth), xylem staining in shoots two or more years old, trunk l and limb lesions (often covered by black, superficial fungal growth), excessive exudation of resin, dieback and death of the tree. Bacteria belonging to the genus Xanthomonas have been suggested as the causal agent. To confirm the constant association between these bacteria and the disease syndrome, the absence of other pathogens and the identity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…Using DNA‐independent and DNA‐based analyses, the pistachio dieback pathogen, previously identified as similar to X. translucens , was found to be phenotypically, biologically and genetically heterogeneous. Two distinct groups were identified, supporting preliminary findings based on five strains (Facelli et al ., 2005). Group A included strains from three areas (Kyalite, Renmark and Red Cliffs) and rep‐PCR revealed genetic variation within this group.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Using DNA‐independent and DNA‐based analyses, the pistachio dieback pathogen, previously identified as similar to X. translucens , was found to be phenotypically, biologically and genetically heterogeneous. Two distinct groups were identified, supporting preliminary findings based on five strains (Facelli et al ., 2005). Group A included strains from three areas (Kyalite, Renmark and Red Cliffs) and rep‐PCR revealed genetic variation within this group.…”
Section: Discussionsupporting
confidence: 84%
“…Strains in group A induced a typical HR on tobacco leaves, indicating that they were pathogenic, whereas strains in group B did not. Groups A and B could also be distinguished by pathogenicity to the Anacardiaceae and Poaceae, whereas a preliminary study with a limited range of strains and hosts failed to reveal differences between groups (Facelli et al ., 2005). Group A appeared to be more aggressive than group B in terms of the HR response, development of symptoms in inoculated plants and recovery of the pathogen from inoculated buds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(E. Facelli, The University of Adelaide, Australia, personal communication) and in 2009 from infected trees in a commercial orchard in Robinvale, Victoria (34°34′46″S, 142°46′47″E, 61 m a.s.l.) (Facelli et al. , 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Discolouration of woody tissue in shoots one or more years old, trunk and limb lesions with excessive exudation of resin, and dieback and death of the tree characterise the disease. Xanthomonas strains have been identified as the causal agent of the disease and previous studies have shown a close relationship between the pathogen and X. translucens (Facelli et al, 2002(Facelli et al, , 2005Marefat et al, 2006). The main location of the pathogen is in the young sapwood of the trunk, primary branches and young branches of diseased trees (Facelli et al, 2003) and the pathogen can be isolated most reliably from woody tissues with internal staining.…”
Section: Introductionmentioning
confidence: 99%